2014
DOI: 10.5144/0256-4947.2014.383
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitudes toward the attire of male physicians: a single-center study in Saudi Arabia

Abstract: BACKGROUND AND OBJECTIVESThe doctor–patient relationship has been influenced by the appearance of physicians, and there is an association between a physician’s physical appearance and the patients’ initial perceptions of physician competence. This study aims to explore patients’ preferences toward the attire of a male physician, and to examine if a physician’s choice of uniform influences the degree of trust, confidence, and follow-up care among respondents.DESIGN AND SETTINGSA cross-sectional survey conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
2
19
2
Order By: Relevance
“…[17] Another interesting study among Saudis found that Western attire with a white coat is preferred by most patients, but the Saudi national dress followed by Western dress is the preferred attire when physicians are dealing with social, sexual, and psychological problems. [18] Internationally, and in contrast to our findings, two studies demonstrated that most patients claimed that attire had no influence on their choice of physician. [13,19] This is clearly an issue related to culture and community values, and accordingly there is a wide variation between different communities in this regard.…”
Section: Discussioncontrasting
confidence: 99%
“…[17] Another interesting study among Saudis found that Western attire with a white coat is preferred by most patients, but the Saudi national dress followed by Western dress is the preferred attire when physicians are dealing with social, sexual, and psychological problems. [18] Internationally, and in contrast to our findings, two studies demonstrated that most patients claimed that attire had no influence on their choice of physician. [13,19] This is clearly an issue related to culture and community values, and accordingly there is a wide variation between different communities in this regard.…”
Section: Discussioncontrasting
confidence: 99%
“…Is has been documented that physician`s attire has an important influence on the patients` trust of physicians, follow their advices, comply with recommendations raised by them, and more likely to return for follow-up care. 10 Another Saudi study reported the same with the exception that patients` confidence in the physician"s ability and the his or her degree of medical knowledge and expertise were not associated with their attire. 4 In agreement with Batais, 10 older patients were more likely to prefer Western uniform more than the Saudi national form.…”
Section: Results:-mentioning
confidence: 68%
“…The same has been reported in another Saudi study carried out in Riyadh. 4 However in another study carried out by Batais in Riyadh also, 10 patients preferred a physician in the Saudi national dress, followed by a physician wearing Western dress.…”
Section: Results:-mentioning
confidence: 99%
“…A study in a family medicine center in Riyadh, Saudi Arabia[ 19 ] showed that participants significantly preferred Western dress (39.9%), followed by Saudi national dress (26.3%), a scrub suit with a white coat (22.3%), and scrubs only (11.5%). Respondents reported that they were more likely to follow medical advice and would return for follow-up care if a physician wore Western dress.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents reported that they were more likely to follow medical advice and would return for follow-up care if a physician wore Western dress. [ 19 ] Results of this study can be used at primary health-care level in the region. Patients attending the study hospitals are the same clients for primary health care.…”
Section: Discussionmentioning
confidence: 99%